(untitled) (Research, Society and Development, 2022)
The maintenance and production of technologies does not distinguish a programmed obsolescence from a marketing vision; however, they are necessary tools for life and as such it is necessary to be instructed with their support and for the conscious and critical use of them. This study aimed to discuss the role of digital technologies and the school’s pedagogical curriculum, defining the use and digital resources in education, verifying the initial and continuing training of teachers for the use of digital tools to know the current scenario of education describing how teachers make use of and prepare for pedagogical use of such technologies. The methodological course has a qualitative nature and includes document analysis, analyzing the Pedagogical Political Projects (PPPs) of two state public schools in Belo Horizonte/MG and knowing the reality of teachers in the face of digital technologies through data collection via an online questionnaire. The results found through this research indicate that the analyzed curricula of the two schools contemplates the understanding of the importance of digital technologies in current education and the continuing education of teachers. Although the two schools demonstrate this understanding in their PPPs, when analyzing their actions with the use of digital technologies the results are very discrepant, noting that the training of teachers in teaching technologies is still timid, almost half of the interviewees do not have training in the area, which is an alarming fact soon after the end of the remote teaching regime.